Nursing Workload and Level of Patient Satisfaction with Nursing Care in Cardiology Department at Tertiary Care Hospitals Pakistan - Hussain, Sabir; RAZZAQ, MUHMOODA ABDUL; SHAH, HAKIM; LASHARI, MUHAMMAD NAWAZ; BHAYO, ABDUL WAHID (Journal of Liaquat University of Medical & Health Sciences, 2021)
OBJECTIVE: The objective of the current study was to analyze nursing workload and patient satisfaction in Civil Hospital, Karachi. METHODOLOGY: A cross-sectional analytical study was conducted at the cardiology department of Dr. Ruth K. M. Pfau Civil Hospital Karachi after approval from the ethical committee and written consent from all enrolled patients. Data were collected from May to October 2018 and a purposive sampling technique was used, a total of 162 patients participated, including age > 18 years and hospital stay > 2 days, and unconscious patients were excluded. Two questionnaires were adopted: Nursing workload and patient safety and modified Heather K. Laschinger Research Tool patient satisfaction with the quality of nursing care questionnaire (PSNCQQ). The data were analyzed through SPSS 20 RESULTS: Higher means (3.91±0.276) score of patient satisfaction was found in the adequate workload group of nurses as compared to more work loaded(2.948 ±1.06) nurses. 04 care-related indicators were significantly associated with nursing workload (Injury, infection, bedsore, allergic reaction from any side effects of medications)while 03 were not significantly associated (urinary tract infection, confused identity of patient and wrong medication) by considering P value<0.05. CONCLUSION: The findings of the study showed that the majority of the patients were satisfied with those nurses who had adequate workload and four care-related indicators were significantly associated with the nursing workload. KEYWORDS: Nurses, Workload, Nursing care indicators, Satisfaction, Cardiology ward, Tertiary Care Hospital.